Mengkaji Alur Cerita dalam Novel Ally Karya Arleena - Katharina Woli Namang; Yeremias Bardi; Maria Palma Vita (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The novel reveals Ally's life, which is not an ordinary life. Often she finds herself placed in a life that seems to belong to her, but is not. And suddenly the word